Current Trends in the Epidemiology and Clinical Aspects of Autoimmune and Autoinflammatory Diseases in Internal Medicine: A Hospital-based Cross-sectional Study - Keïta Kaly; Soukho Assétou Kaya; Sy Djibril; Traoré Djénébou; Cissé Idrissa Ahmadou; Diakité Mahamadou; Dembélé Mamadou; Traoré Abdel Kader; Traoré Hamar Alassane (Research Highlights in Disease and Health Research Vol. 2, 2023)
The epidemiological, clinical, pathophysiological, and immunogenetic characterization of autoimmune and autoinflammatory diseases as a whole would provide relevant clinical and paraclinical clues, therapeutic targets, and preventive medicine approaches in common for some autoimmune and autoinflammatory diseases. Panorama studies of autoimmune and auto-inflammatory diseases are still very little carried out in Africa and particularly in Mali. Here, first of all, the objective of this observational cross-sectional and descriptive study with retrospective data collection for 15 years was to describe the epidemiological and clinical profile of all autoimmune and auto-inflammatory diseases in the department of internal medicine at the University Hospital Center of the Point G. Globally, 6,383 patients were hospitalized in internal medicine at the University Hospital Center of the Point G, of which 317 patients presented with autoimmune and/or auto-inflammatory disease with an average annual hospital recruitment rate of 21 ± 7.87 cases per year. Out of the 317 medical records that met our inclusion criteria,there were 07 cases of association between autoimmune disease and autoinflammatory disease, totaling 14 instances of both autoimmune and autoinflammatory disorders. A total of 331 autoimmune diseases and/or auto-inflammatory diseases were collected, i.e. a frequency of 5.19%, including 291 cases of autoimmune diseases (221 cases of organ-specific autoimmune diseases and 70 cases of systemic autoimmune diseases) and 40 cases of autoinflammatory diseases (no case of monogenic forms, 08 cases of “systemic” polygenic forms and 32 cases of “organ-specific” polygenic forms). Organ-specific autoimmune diseases were dominated by type 1 diabetes (141 cases), Graves’ disease (48 cases) and systemic autoimmune diseases by systemic lupus erythematosus (43 cases), rheumatoid arthritis (16 cases). Among the auto-inflammatory diseases, the “systemic” polygenic forms were dominated by Horton’s disease (02 cases) and the “organ-specific” polygenic forms by gout (16 cases), ulcerative colitis (08 cases). According to our findings, autoimmune and autoinflammatory diseases are characterized in internal medicine by their frequent occurrence in women, preferably between the ages of 25 and 44, with a very disparate distribution. We also found that organ-specific autoimmune diseases outnumbered systemic ones, and "organ-specific" polygenic autoinflammatory diseases outnumbered "systemic" ones.